Implementasi Pembelajaran Kitab Tanbihul Muta'alim Karya Imam Akhmad Maisur Sindi At-Tursidi di Madrasah Diniyah Tathmainnul Quluub Tamanwinangun - Hidayah, Nurul; Faisal, Faisal (IAINU Kebumen, 2026)
The phenomenon of declining morals in the younger generation is an important part of the world of education. Therefore, it is necessary to learn and apply good morals from an early age in everyday life. The author tries to research the learning and application of morals at Madrasah Diniyah Tathmainnul Quluub entitled “Implementation of Learning from the Book of Tanbihul Muta’alim by Imam Ahmad Maisur Sindi At-Tursidi at Madrasah Diniyah Tathmainnul Quluub Tamanwinangun in 2023”. The research objectives are: (1) to find out how the book Tanbihul Muta'alim is taught at Madrasah Diniyah Tathmainnul Quluub Tamanwinangun; (2) to find out how the learning of the Tanbihul Muta'alim book is implemented at Madrasah Diniyah Tathmainnul Quluub Tamanwinangun; (3) to find out what the results of the implementation of learning the book Tanbihul Muta'alim were at Madrasah Diniyah Tathmainnul Quluub Tamanwinangun. This research is in the form of qualitative field research. The students studied were 174 class 2 students at Madrasah Diniyah Tathmainnul Quluub. The method used in this research is qualitative method. The data collected is in the form of learning and implementation data as well as implementation results from the book Tanbihul Muta'alim. The data analysis used is qualitative data analysis. The data analysis techniques used are data reduction, data presentation and drawing conclusions. Based on the research results, the implementation of learning the book Tanbihul Muta'alim went well and the students were able to practice moral teachings in accordance with the contents of the book. Apart from providing material about morals and providing examples of its implementation in daily life, the ustadz also reprimands and gives advice to students whose morals are not good. Apart from that, as an ustadz he also sets a good example for the students, both in terms of words and actions.